A Study of Disinvestment and Privatization Polices of PSU in India - Yadav, Arvind Kumar; Sharma, Vandana (Journal of Commerce and Trade, 2011)
Public enterprises in certain fields are not able to compete with the private enterprises. Their profitability is still not very satisfactory. However, it may be said that profitability is not the only criterion to judge the efficiency of the state enterprises, yet one always expects that there should be a fair rate of return on capital invested in public undertakings because it would otherwise mean a constant drain on capital and the ultimate closure of many undertaking. The term disinvestments are used to indicate the process of privatization. Since the beginning of 1980s, the functioning of the public sector began to be questioned. It was held that the public sector performed well only when protected through state monopolies, entry reservations, high tariffs and quotas etc. Since quite a large number of public enterprises incurred losses year after year, it was argued that the state should not be called upon to meet the losses of these enterprises out of taxpayers, money. In view of the fact that in our country the public sector had entered into too many areas, the question of withdrawing from these areas was also raised. Consequently, the question of privatization of the public sector was debated disinvestment is the process through which privatization could take place. The Disinvestments Ministry should be cautious of transferring PSUs which are milch cows to the private sector by acquiring strategic partnership to the extent of 26%.